Islands ecosystems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
An international symposium on Island ecosystems: a conservation and molecular approach will be hosted by the Centre of Biological and Geological Sciences at the University of Madeira, Portugal, from 5 to 9 March 2001. Conducted in English, the...